Sleep like a baby [compact disc, unabridged] - Harris, Charlaine (Harris, Charlaine. Aurora Teagarden mysteries, 2017)
Robin and Aurora have finally begun their adventure in parenting. With newborn Sophie proving to be quite a handful, Roe's mother pays for a partially trained nurse, Virginia Mitchell, to come help the new parents for a few weeks. Virginia proves to be especially helpful when Robin has to leave town for work and Roe is struck with a bad case of the flu. One particularly stormy night, Roe wakes to hear her daughter crying and Virginia nowhere to be found. Roe's brother Philip helps her search the house and they happen upon a body outside--but it isn't Virginia's. Now, not only does she have a newborn to care for and a vulnerable new marriage to nurture, Roe also has to contend with a new puzzle--who is this mystery woman dead in their backyard, and what happened to Virginia?